RETHINKING RELIGION THEORETICAL AND PRACTICAL APPROACH TO INTERDISCIPLINARY STUDY OF UNDERSTANDING RELIGION IN THE NAGA SOCIETY - Lemwang Chuhwanglim; Yahya Wijaya; Mark Woodward (Universitas Gadjah Mada, 2016)
Religion in society has been a complex study for both academic and non-academic disciplines. Definingreligion had become an issue since the beginning of world religions. This issue will continue to remain insociety, unless world religions avoid imposed definition of religion from the world religions’ perspective.This research aims to study about how religion had been defined by many scholars theologically, politically,culturally, contextually, and how such different approaches never reach the consensus of understandingtoward defining religion. In many cases, the definition of religion was imposed by scholars who havepower of knowledge and intellectual in the discipline of world religions. The power of defining religionfrom the world religions’ perspective becomes challenging for people, such as indigenous people whocontinue to practice their religion from the origin of their fore-parents until today. Religion defined byworld religions from the transcendental perspective had led to discrimination against other indigenousreligions in various parts of the world, such as the Naga people in India.